2020
DOI: 10.1002/cssc.202002411
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Conversion Upgraded by Host‐guest Cooperation between Nitrogen‐Rich Covalent Organic Framework and Imidazolium‐Based Ionic Polymer

Abstract: Invited for this month's cover are the groups of Rongjian Sa and Ruihu Wang at Minjiang University and the Chinese Academy of Sciences. The image shows how host–guest composite catalysts with task‐specific components for the cycloaddition of CO2 with epoxides have been developed through integrating nitrogen‐rich covalent organic framework and imidazolium‐based ionic polymer. The Full Paper itself is available at 10.1002/cssc.202006158.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…The corresponding product was achieved in promising yield (83%) under 2.0 MPa initial pressure at 30 °C for 15 h (Table 1, entry 12). This noteworthy result could allow for the application of Ag@NT‐PPN in chemical fixation of post‐combustion CO 2 [27] …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The corresponding product was achieved in promising yield (83%) under 2.0 MPa initial pressure at 30 °C for 15 h (Table 1, entry 12). This noteworthy result could allow for the application of Ag@NT‐PPN in chemical fixation of post‐combustion CO 2 [27] …”
Section: Resultsmentioning
confidence: 97%
“…This noteworthy result could allow for the application of Ag@NT-PPN in chemical fixation of post-combustion CO 2 . [27] Furthermore, the influence of reaction time on this reaction was illustrated in Figure 5A. The yield of target product increased gradually with reaction time.…”
Section: Catalytic Evaluationmentioning
confidence: 92%
“…However, the preparation of COFs from ionic monomers is difficult as it increases the repulsion between the adjacent layers; thus the successful synthesis usually requires a plethora of error-trials and screens of synthetic parameters (solvent, temperature, time, etc.). 138,141,142 Guanidinium based ILs are a kind of commonly used ionic salt for the synthesis of functional porous PILs. In 2019, Yavuz and co-workers reported the synthesis of guanidinium based porous PILs (COP-213) through the Schiff base condensation of triaminoguanidinium halide and triphenyl benzene β ketoenols.…”
Section: One-step Synthesis Of Porous Pilsmentioning
confidence: 99%
“…Recently, integrating 3‐ethyl‐1‐vinyl‐imidazolium bromide IL polymer (ImIP) with nitrogen‐rich TT‐COF (monomers: 1H‐1,2,4‐triazole‐3,5‐diamine (TDA), 2,4,6‐triformylphloroglucinol (TP)) to construct ImIP@TT‐COF brought the combinatorial innovation for catalyzing cycloaddition reaction of CO 2. [ 40 ] The catalytic reaction was performed under the conditions of 2‐(chloromethyl)oxirane and CO 2 as reactants. The results showed that the yield of 4‐(chloromethyl)‐1,3‐dioxolan‐2‐one was up to 99% with ImIP@TT‐COF as catalyst, in a contrast, the catalytic activity of TT‐COF and ImIP afforded only 43% and 36%.…”
Section: Applications Of Cofs‐ils Compositesmentioning
confidence: 99%